Initial screening of covid-19 patients based on body mass index, blood glucose level and clinical characteristics - Fioni Chandra; Sahna Ferdinand Ginting; Chrismis Novalinda Ginting; Refi Ikhtiari (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: Diabetes Mellitus (DM), chronic metabolic disorder characterized by hyperglycemia causing immune response dysfunction and decontrolled pathogens' spread. DM patients are more vulnerable towards infection. Regarding COVID-19 infection, it is essential and urgent to develop initial screening of DM or non-DM patients to establish effective clinical treatment.Objective: Understanding the implementation of initial screening for Diabetes Mellitus based on Blood Glucose Level (BGL) and Body Mass Index (BMI) as guidance in clinical care and how it affects BGL and clinical parameters of DM and non-DM patients indicated positive COVID-19.Methods: This research uses cohort retrospective study. COVID-19 patients in Royal Prima Hospital Medan match the purposive sampling inclusion criteria included in the research for further review through patient’s medical record. 168 samples were divided into 54 DM and 114 non-DM patients. The variables are BMI and BGL. Data will be analyzed using Independent Sample T-Test.Results: Clinical characteristics of COVID-19 patients are dyspneu, chest pain, cough, fever, epigastric pain, etc. Result shows that majority of respondents have normal BMI without DM (72.8%). The Independent Sample T-Test analysis result shows a significant difference in BMI and BGL between DM and non-DM patients.Conclusion: Clinical evidence shows significant differences in BMI and BGL between DM and non-DM patients with COVID-19. Thus, BMI and BGL could be used as the initial screening to develop effective clinical treatment of controlled BGL of DM and non-DM COVID-19 patients based on clinical parameters evaluation.